Ethanol steam reforming with a Ni–BaZr0.1Ce0.7 Y0.1Yb0.1O3–δ catalyst. (June 2019) - Li, Nanqi; Pu, Jian; Chi, Bo; Li, Jian
Abstract: BaZr0.1 Ce0.7 Y0.1 Yb0.1 O3–δ supported Ni catalyst is prepared by sol-gel and precipitation methods and evaluated as a catalyst for ethanol steam reforming. This catalyst demonstrates 100% conversion of ethanol into various amounts of H2, CO, CO2, CH4 depending on reforming temperature in the range between 500 and 750 °C. The yield of H2 –CO reaches around 85% at temperatures below 600 °C and decreases to the level of 80% at 650 and 750 °C, and the amount of CH4 in the reformate is below 10% at all these temperatures. Decreasing H2 O/ethanol ratio from 5 to 3 does obviously change the yield of H2 –CO, and increasing temperature promotes H2 and CO2 and depresses CO formation. The BaZr0.1 Ce0.7 Y0.1 Yb0.1 O3–δ in Ni–BaZr0.1 Ce0.7 Y0.1 Yb0.1 O3–δ decomposes into BaCO3 and CeO2 based oxide in ethanol steam reforming atmosphere at all the temperatures, and this decomposition starts since 5 h of the reforming at 750 °C. Carbon deposition is observed in Ni–BaZr0.1 Ce0.7 Y0.1 Yb0.1 O3–δ during 24 h reforming tests at 500 and 600 °C, but it is much more resistant to coking than catalysts with precious metals and Ni supported on other types of oxides. Highlights: Ni-BZCYYb catalyst for ethanol steam reforming (ESR) developed. Complete conversion and high selectivity of H2 –CO obtained. BZCYYb decomposed in ESR environment into BaCO3 and CeO2 based oxide. Coking resistance unchanged regardless of decomposition.